TINJAUAN YURIDIS ATAS GRATIFIKASI YANG DIPERKARAKAN DI PENGADILAN TINDAK PIDANA KORUPSI SAMARINDA DALAM PERSEPEKTIF HUKUM PIDANA INDONESIA - Beni Fernandes Hibur (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTION            Gratifikasi is not type glare at but as element glare at, as for glaring at of own is receiver of Gratifikasi which oppose against its obligation and its duty, Congeniality of GRATIFIKASI there are Clarification of Section 12B Sentence ( 1) UU No.31 Year 1999 as altered with UU No.20 Year 2001, that : " such with " gratifikasi" in this sentence is gift in wide of meaning, namely cover gift of money, goods, rebate (discount), commission, interest free loan, journey ticket, lodging facility, vication, medication free, and other facility. The gratifikasi both for accepted in country and also beyond the sea and which is conducted by using electronic medium or without electronic medium."             If is careful of formula above hence clarification of section 12B ( article 1 ) of sentence which including gratifikasi is limited to sentence : giving in wide of meaning, while sentence afterwards represent forms of gratifikasi. And assured in section 12 letter of B sentence ( 1) as also to That is each;every gratifikasi to Public Servant assumed to bribe, if relating to its occupation and adversative with obligation or its duty. In formula at section 12B can comprehend that do not all that gratifikasi illegal but only gratifikasi fulfilling element of just pasai 12B is and is later then seen from ITS criminal law of him of KUHPPIDANA in Chapter of XXVIII ( Section 418, 419, and 420 ) arranging about occupation crime. Keyword: Gratifikasi, Corruption, Collutio and Nepotism.